PENERAPAN PENDEKATAN REALISTIC MATHEMATIC EDUCATION (RME) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR METAFORA PESERTA DIDIK SMP - Nurfitri Nurfitri; Dinny Mardiana (Universitas Islam Nusantara, 2019)
The research was motivated by low students’ thinking ability. One of alternative that can be applied to improve students'metaphorical thinking ability was the Realistic Mathematic Education (RME) approach. The aims of this study was findout the improvement of students’ metaphorical thinking ability using RME approach compared with conventional learning,and students' response to mathematics learning using RME approach. The research method was quasi-experimental method,with non equivalent pretest-posttest control group design. The research was conducted in one of the Private Junior HighSchools in Sumedang District. The research population was all students of class VIII, class VIII C as experimental classand VIII D as control class. RME approach was given to the experimental class, while conventional learning was given tothe control class. The instruments used were metaphorical thinking skills test, student's questionnaire, and observation sheetsof educator. The results of the research are qualitative and quantitative datas. Based on the analysis of metaphorical thinkingability test results obtained conclusion: improvement of students' metaphorical thinking ability by using RME approachbetter than students with conventional approach, and students’ respond positively to learning mathematics by using RMEapproach